A comparative analysis of canyon and non-canyon populations of the deep-sea scavenging amphipod Paralicella caperesca. (21st December 2015) - Duffy, Grant A.; Gutteridge, Zoe R.S.; Thurston, Michael H.; Horton, Tammy
Abstract : Existing population studies of deep-sea amphipods have focused on species that inhabit deep-sea vent or trench environments but few cosmopolitan species have been studied. Here we provide new insight into the life history and population ecology of the pan-oceanic scavenging amphipod Paralicella caperesca and discuss the influence of nutrient-rich submarine canyon environments on the growth and reproduction of this species. Data were collected through the dissection and measurement of 2997 P. caperesca from 14 samples taken from abyssal plains, continental slopes and submarine canyons in the North-East Atlantic. Sexual dimorphism was less pronounced than observed for other scavenging amphipod species but females were significantly larger and had shorter antennae than males. The size of oostegites in female P. caperesca varied considerably within size classes, ovaries contained a relatively large number of oocytes, and no empty ovaries were observed. These factors, in combination with absence of mature females, suggest that P. caperesca practices semelparity, a reproductive strategy that complements the feeding strategy of this obligate necrophage. Five male and seven female size-grouped cohorts were identified for P. caperesca . Cohorts from deep-sea submarine canyon populations showed consistently larger mean total body lengths than non-canyon cohorts. Individuals from canyon samples also expressed sexual characteristics at smaller sizes than non-canyon individuals. We hypothesize that these trends are indicative of nutrient-mediated growth, maturation, and reproduction in P. caperesca . The species is able to grow and reproduce relatively quickly in response to increased nutrient input in canyon environments and therefore dominates scavenging amphipod assemblages.